Znaczenie Pokolenia ’98 dla narodowej oraz intelektualnej tożsamości Hiszpanów - Kruszyńska, Kamila (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article presents the characteristics of Spanish modernism. The author points to a group of writers known as Generation ’98, whose shared characteristic was their focus on the criticism of the socio-political situation of their country in the late nineteenth and early twentieth century. The key representatives of the group are: Miguel de Unamuno, José Martínez Ruiz (Azorín), Pío Baroja, Ramiro de Maeztu, and Ramón del Valle-Inclán. The first section of the paper outlines the specific qualities of the literary output and attitudes of the Generation ’98 writers, distinct from modernism as such. The second part focuses on the attitude of thinkers to Spain and Spanishness, as well as intellectual consequences thereof. The final part presents a critique of that trend and its interpretation.